Gender differences in dictator giving: A high-power laboratory test. - Iván Barreda-Tarrazona; Ainhoa Jaramillo-Gutiérrez; Marina Pavan; Gerardo Sabater-Grande (PLoS ONE)
We gather information from a large laboratory sample comprising 1,161 subjects and study gender differences in altruism using a dual-role dictator game. We control for factors potentially affecting the role of gender in dictator giving, such as the subject's age, cognitive ability, and personality traits, together with the dictator's self-reported emotions motivating the decision, and response time. We find that women behave in a significantly more generous way than men: after controlling for the factors mentioned above, females transfer 7.5 percentage points (about 40%) more of their endowment than males, on average. Moreover, we find that gender differences in giving are mediated by reasoning ability, personality traits and emotions.